Answer:
![x=\pm√(y+64)](https://img.qammunity.org/2022/formulas/mathematics/high-school/xaau5psnzzd3znchj67xtq1wasqwubhkv8.png)
Explanation:
All you need to do is isolate the x.
First, add 64 to both sides:
![y=x^2-64\\x^2-64+64=y+64\\x^2=y+64](https://img.qammunity.org/2022/formulas/mathematics/high-school/a68uqwb13j7rioze1ajc99fd9agv632zan.png)
Then, take the square root of both sides:
![√(x^2)=√(y+64)\\x=\sqrt{y+64](https://img.qammunity.org/2022/formulas/mathematics/high-school/cmoblud7j4bjfe80m8m3nmpasip3ybomvn.png)
Actually, that is:
![x=\pm√(y+64)](https://img.qammunity.org/2022/formulas/mathematics/high-school/xaau5psnzzd3znchj67xtq1wasqwubhkv8.png)
Here's the reason for that. An example would be:
![x^2=4](https://img.qammunity.org/2022/formulas/mathematics/high-school/yhaojeyv3skg2u0m9an1o2p3md0vfp9pq9.png)
Here, you'd take the square root of both sides to solve for x.
![√(x^2)=√(4)\\x=2](https://img.qammunity.org/2022/formulas/mathematics/high-school/gxzchmi4cb8hnp8fhbtfe93bcdimnaoqa9.png)
Right? But X could also be a -2, because a negative times a negative is a positive.
![(-2)^2=4\\-2*-2=4\\4=4](https://img.qammunity.org/2022/formulas/mathematics/high-school/cj5nf5lyd5f2gp1csxl0mamvzkprblxciy.png)
Therefore,
or
![x=\pm2](https://img.qammunity.org/2022/formulas/mathematics/high-school/pish7su1v2iqigtp17nww3bjo0ik2tcey1.png)
![x^2=2*2=4\\x^2=-2*-2=4](https://img.qammunity.org/2022/formulas/mathematics/high-school/w30u86awgsg5rf6hwu1mqrlpahaekkfdyy.png)